Two-photon imaging with diffractive optical elements - Watson, Brendon O.; Nikolenko, Volodymyr; Yuste, Rafael (Frontiers in Neural Circuits, 2009)
Two-photon imaging has become a useful tool for optical monitoring of neural circuits, but it requires high laser power and serial scanning of each pixel in a sample. This results in slow imaging rates, limiting the measurements of fast signals such as neuronal activity. To improve the speed and signal-to-noise ratio of two-photon imaging, we introduce a simple modification of a two-photon microscope, using a diffractive optical element (DOE) which splits the laser beam into several beamlets that can simultaneously scan the sample. We demonstrate the advantages of DOE scanning by enhancing the speed and sensitivity of two-photon calcium imaging of action potentials in neurons from neocortical brain slices. DOE scanning can easily improve the detection of time-varying signals in two-photon and other non-linear microscopies.